Insights how expert principals make difficult decisions - McLaughlin, Dionne V. (Corwin, 2015)
"Essential to inspiring and improving schools, principals make complex decisions on a daily basis. This invaluable resource offers extensive case studies to explore how expert principals manage crises, navigate tough choices, and support school environments. A former elementary and secondary school site administrator, the author presents a highly sensible, cohesive, and research-based approach to decision making that will greatly benefit school principals at any career stage"--Back cover.